1994
DOI: 10.1037/1064-1297.2.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking and smoking deprivation on Wisconsin Card Sorting Test performance.

Abstract: Wisconsin Card Sorting Test (WCST) performance was assessed in 24 heavy smokers and 12 nonsmokers recruited from universities in the United States and Japan. Half of the smokers performed the WCST after abstaining from tobacco for 12 hr, whereas the remaining smokers smoked a cigarette of their preferred brand immediately before the test. Nonsmokers did not smoke. The WCST was administered by computer, first with standard instructions and then a second time with abbreviated instructions that specified the 3 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
3
21
1
Order By: Relevance
“…The nonselective effect on both perseverative and nonperseverative types of errors suggests a nonspecific cognitive enhancing effect of the drug in LCCs rather than a specific effect on cognitive processes mediated by the prefrontal cortex. The absence of any apparent effect of caffeine on WCST performance in HCCs suggests simple tolerance without abstinence or restorative effects, and can be contrasted with the restorative effects of nicotine on WCST performance in heavy smokers (Lyvers et al, 1994). The present findings thus did not support the hypothesis in James (1997) that improvement in performance following caffeine is generally due to reversal of withdrawal-induced deficits.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The nonselective effect on both perseverative and nonperseverative types of errors suggests a nonspecific cognitive enhancing effect of the drug in LCCs rather than a specific effect on cognitive processes mediated by the prefrontal cortex. The absence of any apparent effect of caffeine on WCST performance in HCCs suggests simple tolerance without abstinence or restorative effects, and can be contrasted with the restorative effects of nicotine on WCST performance in heavy smokers (Lyvers et al, 1994). The present findings thus did not support the hypothesis in James (1997) that improvement in performance following caffeine is generally due to reversal of withdrawal-induced deficits.…”
Section: Discussioncontrasting
confidence: 56%
“…A fully between-subjects design was employed because of the strong effects of repeated testing on both WCST performance (Lyvers & Maltzman, 1991b) and SCRs (Lyvers, Boyd, & Maltzman, 1988), which would likely obscure caffeine effects or complicate their interpretation. T o qualify for inclusion in the study, participants were required to (a) be between the ages of 18 to 35 years; (b) be nonsmokers, to avoid nicotine effects on WCST and SCR measures (Lyvers & Miyata, 1993;Lyvers et al, 1994); (c) report typical caffeine intake that met the above criteria for either HCC or LCC; (d) have no prior history of treatment or arrest for illicit drug-or alcohol-related problems; and (e) normally consume no more than 14 standard alcoholic drinks per week. T o recruit subjects, flyers were posted on the campuses of Bond and Griffith-Gold Coast Universities and an email request was sent to all Bond students.…”
Section: Participantsmentioning
confidence: 99%
“…People with frontal lobe damage tend to make perseverative responses (PRs) and errors (PEs) (Robinson et al, 1980) on this test. The dual run procedure used in the present study has been shown to increase the sensitivity of the Neuropsychological Correlates of Opioid Dependence 4 WCST to frontal lobe dysfunction (Stuss et al, 1983) and drug effects (Lyvers & Maltzman, 1991;Lyvers et al, 1994) and more selectively activates the prefrontal cortex than the standard procedure does (Berman et al, 1995;Smith et al, 1997). In recognition of their sensitivity to prefrontal cortex dysfunction (Mountain & Snow, 1993), the crucial WCST measures in the present study were the percentages of responses that were PEs (%PE) and PRs (%PR), with the percentage of responses that were nonperseverative errors (%NPE) serving as a control index of nonspecific cognitive impairment.…”
Section: Profile Of Mood States (Poms;mentioning
confidence: 99%
“…Previous research by Lyvers and colleagues (Lyvers & Maltzman, 1991;Lyvers, Maltzman & Miyata, 1994) has shown that the Wisconsin Card Sorting Test (WCST), a widely used index of executive cognitive functioning, is surprisingly sensitive to the effects of mild psychoactive doses of alcohol or nicotine. Measures of perseveration selectively distinguished drug from placebo or withdrawal conditions; perseveration measures are consistently elevated in persons who have suffered frontal lobe injury (Robinson, Heaton, Lehman, & Stilson, 1980).…”
mentioning
confidence: 99%
“…In nicotine-dependent individuals, tobacco deprivation can impair attentional and cognitive abilities within 12 h of smoking cessation (Bell et al 1999;Gross et al 1993;Lyvers et al 1994), and nicotine administration or cigarette smoking can reverse such deficits to predeprivation performance levels (Bell et al 1999;Parrott and Roberts 1991). Whether improved performance associated with relief from withdrawal should be considered cognitive enhancement has been questioned (Heishman et al 1994;Hughes 1991).…”
mentioning
confidence: 99%